The once and future geek - Mancusi, Mari (Mancusi, Mari. Camelot code, 2019)
When thirteen-year-old Arthur of Gal, the future King Arthur of Camelot, accidentally time-travels to the twenty-first century and learns what is in store for him after pulling the sword from the stone, he decides to stay in the future and join the football team instead. Now it's up to gamers and best friends Sophie and Stu to convince him to return and correct the timeline, while avoiding Lady Morgana who has followed Arthur to kill him and seize the throne.